"I function when I'm painting" – Consumers, carers and staff experiences of an art and mental health recovery project in Fiji. (February 2022) - Fenner, Patricia; Ryan, Brigid; Nabukavou, Thelma; Chang, Odille; Chetty, Salochana; Qaloewai, Sefanaia
Abstract: This study sought to extend understanding of the role of art making and mental health recovery in the Pacific context, specifically in Fiji. Results from a focus group study highlighted the functions and meanings to participants of a year-long art-making program designed locally and undertaken with consumers, carers and mental health staff. Participants found an increased sense of self-worth, safety in the group similar to that experienced in a family, extended social capacities, and the role of the facilitator to be vital, amongst the outcomes. Unlike in previous similar research, this study highlighted the contribution of utilisation of local traditional art materials and processes to enhance a sense of purpose and achievement for participants, in particular for consumers. Highlights: Cultural values meaningful in the Fijian context inform art making and mental health recovery research. Traditional materials and art processes lead therapeutic art making. Engagement of all stakeholder groups in study design, procedures and realisation.